Enlarging Skull Fractures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1995)
The diagnosis, management, and treatment of large unhealed skull fractures are reported in 10 children, aged 2 weeks to 27 months, seen at the Children's National Medical Center, Washington, DC in a 4 year period.